Вплив особливостей контактної взаємодії тонкої штаби з валками на параметри початкового налаштування робочої кліті і найменшу товщину штаби, що прокатується - Василев, Я.Д.; Замогильний, Р.О. (Physico-technological Institute of Metals and Alloys, 2023)
The features of the force interaction of a thin strip with rollers and with a working stand as a whole during cold rolling are investigated. It is shown, that during cold rolling of thin strips, the elastic deformations of the rolls and the strips have a decisive influence on the linear rolling force Pc /b. The data are presented confirming, that the formation of the strip thickness during rolling occurs as a result of the joint interaction of the strip with the work rolls and with the working stand as a whole. Due to the low modulus of stiffness of the working stands, Мкл (Мкл = 4.5–7.5 MN/mm) of the cold rolling mills in operation, the elastic deformations of the last δкл are many times greater than the thickness of the strip at the exit from the deformation zone h1 (δкл >> h1) and the rolling process is always implemented in pre-pressed rollers with a power Рпр, which limits the ability of the equipment for rolling strips of small thickness. With a decrease in the thickness and width of the strip b due to a decrease in the parameter b/L (where L is the length of the roll barrel), the end sections of the barrels of the work rolls in the rolling process are also in the “bottom face”, i. e. pressed force Pз, which is summed with the force rolling Pс, which leads to additional loading of the rolls and, as a consequence, to an additional limitation of the equipment for rolling strips of smaller thickness. For the first time, the problem of determining the parameters of the initial setting of the working stand during rolling was solved, when the end sections of the work rolls are in the “bottom” during the rolling process and a solution is proposed for determining the smallest strip thickness h1нм, that can be rolled on a particular mill. The experimental verification of calculation of the parameters of the initial setting and the smallest thickness of the strip, which can be rolled up at a specific state h1нм, confirmed the efficiency and sufficient accuracy of the proposed solutions, which makes it possible to recommend them for practical application in expanding the range of products produced in operating states in the direction reducing the thickness of the strip that are rolled out and designing the assortment at the new mills for the rolling of thin and especially thin strips, including tinplate and foil.